Pengembangan Simulator Perangkat I/O dengan Pemrograman Ekspresi Boolean dan Javascript - Pratikto Pratikto; Raydha Zul Fitriani (Retii, 2018)
Boolean expressions are an important result of a translation algorithm from a ladder diagram. Having a PLC and a ladder diagram on digital device programming has grown, VHDL requires translating back to boolean expressions that are equivalent to ladder diagrams to run in the program. Elements of ladder diagram-based programming not only consist of basic operations such as And, Or, or Not, but also contain additional basic elements such as comparators, timers and counters. In this paper we discuss a script-based programming that contains boolean expressions for each row of scripts, but represents a rung of a ladder diagram. Script-based programming developed using Javascript boolean expressions syntax is expected to be the beginning of a new way of programming I/O devices in addition to existing Structured Text programming methods. An I/O simulator based on web programming was built to visualize the written boolean expressions. The script consists of two parts, the main part is boolean expressions beside of scripts for graphical and other visualizations adapted to the Javascript writing syntax. Programing with use boolean expressions of ladder equivalents are more concise and minimize broad view in testing the course of programs with additional visualization of results. The timer algorithm is designed to be applied on a second time scale. The error value for on delay is around 0.062 seconds and for off delay around 0.046 seconds.Keyword: Boolean expressions, ladder, I/O, Javascript, simulator